A detailed comparative investigation on structural, technofunctional and bioactive characteristics of protein concentrates from different common bean genotypes - Karaman, Kevser; Bekiroglu, Hatice; Kaplan, Mahmut; Ciftci, Beyza; Yueruerdurmaz, Cengiz; Sagdic, Osman (ELSEVIER, 2022)
In this study, a comparative investigation on the structural, technofunctional and bioactive properties of protein concentrates from different common bean genotypes was performed. Protein extractions were carried out at different pH and salt concentrations and the highest protein content for the concentrates (77.7%) was determined for pH 11 and 0.4% of salt. The protein content of the common bean flour and their protein concentrates was in the range of 22-26.93% and 72.97-77.99%, respectively. For bioactive properties, total phenolic content ranged between 578.9 and 1355.9 and 313.5-1219.1 mg GAE/kg, for bean flours and protein concentrates, respectively. Two genotypes (G7 and G8) were the samples showing the superior biofunctional properties compared to the others. Thermal characterization showed that Td and Delta H values were in the range of 64.95-94.33 degrees C and 76.64-122.3 j/g, respectively. SDS-PAGE analysis revealed that the major band corresponded to the 7S vicilin. Principal component analysis showed that G2 and G6 had different characteristics in terms of technofunctional parameters while G7 and G8 were differed from the other genotypes in terms of bioactivity. The results showed that the proteins of common beans could be evaluated as good source due to high bioactivity for the enrichment of food formulations.
Keywords: Bean protein; Genotype; SDS-PAGE; Bioactivity; FUNCTIONAL-PROPERTIES; PHYSICOCHEMICAL PROPERTIES; L.; PEA; CHICKPEA; EXTRACTION; GLOBULINS; STABILITY; PEPTIDES; LEGUMES; Biochemistry & Molecular Biology; Chemistry; Polymer Science